2012
DOI: 10.1007/s10202-012-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Service robots in the mirror of reflective research

Abstract: Service robotics has increasingly become the focus of reflective research on new technologies over the last decade. The current state of technology is characterized by prototypical robot systems developed for specific application scenarios outside factories. This has enabled context-based Science and Technology Studies and technology assessments of service robotic systems. This contribution describes the status quo of this reflective research as the starting point for interdisciplinary technology assessment (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…During trials, it has been observed that some persons with physical or mild cognitive impairment prefer using voice commands to touchscreen control of the devices (Portet et al, 2011), while others found the touchscreen control equally beneficial (Wallace et al, 2010). In a discussion of the use of robots, Decker (2012) emphasises that although it is recommended that a veto function should exist to allow users to stop the robots' actions, this view has been challenged where persons with cognitive impairment are concerned. Also, some authors point out that during a trial, the participants had to be protected against information overload (Duquenoy and Whitehouse, 2006;Kang et al, 2010).…”
Section: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…During trials, it has been observed that some persons with physical or mild cognitive impairment prefer using voice commands to touchscreen control of the devices (Portet et al, 2011), while others found the touchscreen control equally beneficial (Wallace et al, 2010). In a discussion of the use of robots, Decker (2012) emphasises that although it is recommended that a veto function should exist to allow users to stop the robots' actions, this view has been challenged where persons with cognitive impairment are concerned. Also, some authors point out that during a trial, the participants had to be protected against information overload (Duquenoy and Whitehouse, 2006;Kang et al, 2010).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In principle, the owner of a service robot is liable for the damages caused only if he or those assisting him are personally responsible. Mistakes in the production or instructions of a product are the responsibilities of the manufacturer (Decker, 2012). However, the liability of the owner is again questionable, if such a robot adapts autonomously to various situations, or can react to human beings, other robots or the environment.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…All the presentations were followed by very interesting and constructive discussions that enabled us to understand the TA dimension when robotics is introduced into working environments. The interest for this debate is even larger because the implications of robotics in our daily life are still growing very quickly as a result of the increasing number of industrial robots (still growing with high rates of growth) and the emergence of new service robots and their application in a wide variety of sectors (Krings et al, 2014;Decker, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Assistive service-robots offer some potential to meet occurring challenges in health care caused by severe demographic changes (Robinson, MacDonald and Broadbent, 2014). Robots assisting older people to manage their everyday life need to perform a variety of tasks, interact flexibly, and adapt to a wide range of capabilities and health constraints in non-standard situations and environments (Decker, 2012).…”
Section: Introductionmentioning
confidence: 99%